PEMANFATAAN MEDIA SOSIAL FACEBOOK SEBAGAI STRATEGI KOMUNIKASI POLITIK - Suratno Suratno; Irwansyah Irwansyah; Niken Febrina Ernungtyas; Guntur Freddy Prisanto; Safira Hasna (SOURCE : Jurnal Ilmu Komunikasi, 2020)
Political candidates are actively using Facebook's social media as a political communication strategy, for which there is social interaction and interactive dialogues between the candidates and the public in  virtual space, where this is needed to influence public involvement in achieving their political missions. Therefore, the objective of this study is to describe the influence of the use of social media Facebook as a political communication strategy on the electability, effectiveness, and popularity of the candidates of the DPR RI members in 2019 legislative elections. The research used theories and concepts of political communication and the use of social media in political communication, using quantitative research methods and surveys of 30 Facebook user respondents and voters in the 2019 legislative elections. The results showed there was an impact of Facebook utilization on the electability by  16%, on effectiveness by  39.7%, and on the popularity of prospective members of the DPR RI in the 2019 legislative elections by  17.3%. Users can actively collect information and opinions using this site as a place of communication between themselves with the politicians or with fellow supporters. However, the use of Facebook is not the only effective political communication strategy, traditional media such as television, radio, billboards, stickers are still effective to reach the public who do not always use social media.